Application of geomorphic principles to environmental management in semiarid regions - Schumm, Stanley Alfred, 1927-, author; Bradley, M. T., author; Begin, Z. B., author; Colorado Water Resources Research Institute, Colorado State University, publisher (Colorado State University. Libraries, 1980)
The incision of gullies into valley alluvium is a severe soil conservation problem, resulting in deterioration of agricultural land, sediment pollution, filling of reservoirs, and water table lowering in the valley floor. Therefore, it is of importance to identify as accurately as possible those valleys which are prone to gullying, in order to establish priorities for soil conservation treatment within a geomorphically similar area. In other words, what is needed is an operational definition of the geomorphic threshold above which gully incision into the valley alluvium occurs. In many valleys of the semiarid west valley floors are either flat and vegetated without a channel, or they are gullied. It will be of value to establish under what conditions the stable valley floor is incised by discontinuous gullies. Normally the explanation is a large storm, overgrazing or other man-induced changes; however, the character of the valley floor also plays an important role. The valley floor itself can provide a means of recognizing incipiently unstable conditions that lead to incision. Using previously collected data from the Piceance Creek area of western Colorado, it is possible to identify a valley-slope threshold above which, for a given drainage area, gullying is certain. Below this valley-slope threshold the valley floors are stable; above it they are susceptible to gullying. When the relations and techniques developed in western Colorado were applied to a similar situation in northeastern Colorado, the Chalk Bluffs area, it was determined that valley width was also a significant factor determining valley stability, and a ratio of valley slope to valley width could be used to identify at a given drainage area a threshold zone of valley floor instability. These relations explain the observed variability of gullies and also permit identification of those locations where gullying is probable.
Submitted to Office of Water Research and Technology, U.S. Department of the Interior.
February 1980.
Keywords: Arroyos -- Colorado; Arid regions -- Colorado; Soil erosion -- Colorado